KAJIAN INTERAKSI ANTAROBAT DAN HUBUNGANNYA DENGAN POLIFARMASI PADA PASIEN SKIZOFRENIA - Andi Ahriansyah; Mutawalli Sjahid latief (IONTech Journal, 2026)
Schizophrenia is a chronic mental disorder affecting thought processes, perception, affect, and behavior, requiring long-term pharmacotherapy. In routine practice, patients frequently receive multiple concurrent medications (polypharmacy) to control psychiatric symptoms and manage comorbid conditions, which may increase drug-related problems, particularly potential drug–drug interactions (pDDIs). This study aimed to identify pDDIs and examine their association with the number of prescribed drugs among outpatients with schizophrenia at a public hospital in Jakarta. A retrospective analytical cross-sectional study was conducted from January to June 2025. From 357 outpatients, 15 medical records met the inclusion criteria (age ≥18 years, schizophrenia as the primary diagnosis, complete demographic/clinical and medication data, and at least two drugs per visit). Patient characteristics and medication profiles were collected. pDDIs were identified based on drug combinations and categorized by severity. The association between the number of drugs (<3 vs ≥3) and pDDIs was assessed using chi-square testing with odds ratio (OR). Most patients were aged 46–55 years (53.3%), and 73.3% had no documented comorbidities. The most frequently prescribed antipsychotics were risperidone (46.7%) and clozapine (33.3%), and 66.7% of patients received ≥3 drugs. pDDIs were detected in all prescriptions (15/15; 100%), totaling 26 events, predominantly moderate (73.08%) rather than major (26.92%). The most common interaction was risperidone–trihexyphenidyl (15.38%). No statistically significant association was found between the number of drugs and pDDIs (p=0.591; OR 0.444; 95%CI 0.022–9.032). These findings highlight the need for ongoing medication review and clinical pharmacy services to mitigate interaction risks, particularly involving antipsychotics and concomitant therapies.